Postoperative Myocardial Reinfarction Following Lumbar Spine Surgery. Issue 1 (February 2022) - Harwin, Brett; Roberts, Sidney; Formanek, Blake; Wang, Jeffrey C.; Buser, Zorica
Abstract : Study Design: This study was a retrospective cohort database study which looked at the relationship between myocardial reinfarction following lumbar spine surgery. Objective: Current study aimed to determine the risk of reinfarction associated with the time between initial myocardial infarction (MI) and lumbar spine surgery, type of lumbar surgical procedure, and other risk factors. Summary of Background Info: Several studies have demonstrated a strong temporal pattern between postoperative reinfarction rate and the period between previous MI and surgery. To the best of our knowledge, no study has looked specifically at the temporal relationship between previous MI, lumbar spine surgery and incidence of postoperative myocardial reinfarction. Materials and Methods: The Humana database was analyzed from Q1 2007 through Q3 2016 and the Medicare database was analyzed from Q1 2005 through Q4 2014. Patients were placed into 1 of 5 groups based on time between MI and surgery: 0–3, 4–6, 7–12, 13–24, and 25+ months. Reinfarction rates were determined in these groups. Age, sex, and type of surgery were analyzed to determine association with postoperative reinfarction rates. Results: There was a strong correlation between postoperative myocardial reinfarction and lumbar spine surgery occurring 0–3 months after the patient's initial MI ( P <0.01). Those patients had a risk ratio >3 ( P <0.01) compared with patients who underwent lumbar spine surgery after an interval >3 months between initial MI and lumbar spine surgery. In addition, spinal fusion procedures were associated with a greater risk of postoperative myocardial reinfarction than nonfusion procedures. Conclusion: In both databases, there was a clinically relevant and statistically significant increase in myocardial reinfarction in patients who experienced an MI 0–3 months before lumbar spine surgery. We believe that the current study helps in treatment planning for patients with a history of MI who are considering spine surgery. Level of Evidence: Level III.